Penerapan Prinsip Efisiensi Dan Efektivitas Dalam Pendaftaran Penduduk Melalui Website Sintren Sebagai Perwujudan Prinsip Good Governance - Siti Deliana Rachmayanti; Sri Nurhari Susanto; Suhartoyo Suhartoyo (Administrative Law and Governance Journal, 2022)
Abstract: The Gegesikkidul Village Government organizes a population registration service using the SINTREN website, in order to provide convenience for the community in the village and to apply the principles of efficiency and effectiveness in services in order to realize good governance. The purpose of this study is to find out how to apply the principles of efficiency and effectiveness and to find out the inhibiting factors contained in population registration through the SINTREN website at the Gegesikkidul Village Government. The research method used is juridical empirical. The results of the study indicate that policy making regarding Gegesikkidul Village Government as a facilitator between the community and the SINTREN website to provide and improve services for village communities. The existence of indicators that have not been met and the existence of inhibiting factors in the implementation of services causes the application of the principles of efficiency and effectiveness in population registration through the SINTREN website as the embodiment of good governance in the Gegesikkidul Village Government that cannot be implemented perfectly. Keywords : efficiency, effectiveness, population registration, Sintren website Abstrak: Pemerintahan Desa Gegesikkidul menyelenggarakan suatu pelayanan pendaftaran penduduk dengan menggunakan website SINTREN, guna memberikan kemudahan bagi masyarakat di desa serta untuk menerapkan prinsip efisiensi dan efektivitas dalam pelayanan agar terwujudnya pemerintahan yang baik. Tujuan penelitian ini yaitu, untuk mengetahui bagaimana penerapan prinsip efisiensi dan efektivitas serta untuk mengetahui faktor penghambat yang terdapat dalam pendaftaran penduduk melalui website SINTREN di Pemerintahan Desa Gegesikkidul. Metode penelitian yang digunakan adalah yuridis empiris. Hasil penelitian menunjukkan bahwa pengambilan kebijakan mengenai Pemerintahan Desa Gegesikkidul sebagai fasilitator antara masyarakat dengan website SINTREN untuk memberikan serta meningkatkan pelayanan bagi masyarakat desa. Terdapatnya indikator yang belum terpenuhi serta adanya faktor penghambat dalam penyelenggaraan pelayanan menyebabkan, penerapan prinsip efisiensi dan efektivitas dalam pendaftaran penduduk melalui website SINTREN sebagai perwujudan good governance di Pemerintahan Desa Gegesikkidul belum dapat diterapkan secara sempurna. Kata kunci : Efisiensi, Efektivitas, Pendaftaran Penduduk, Website SINTREN